External and Internal Forcings for Hypoxia Formation in an Urban Harbour in Hong Kong - Lu, Zhongming; Yu, Liuqian; Gan, Jianping (Frontiers in Marine Science, 2022)
Eutrophication-driven hypoxia is one of the reasons for the deterioration of coastal waters, especially those adjacent to densely inhabited urban cities. Thus, effective hypoxia management is urgently needed, and quantitative knowledge of factors controlling hypoxia is required. A case in point is the coastal water around Hong Kong, a megacity that has over 7.5 million residents and is located downstream of the large and nutrient-rich Pearl River. The Victoria Harbour (VH) is the core area of Hong Kong water and has been suffering from marine environment deterioration for years because of external biogeochemical influxes from adjacent waters and internal physical and biogeochemical responses. Three channels orienting from south to north (C1), southeast to northwest (C2), and west to east (C3) connect the VH to adjacent waters and serve as the primary exchange pathways for water mass and biogeochemical substances. Using observational data and a coupled physical–biogeochemical model, we showed that the northward transport of low dissolved oxygen (DO) water from the coastal transition zone by the shoreward bottom current mainly through C1 directly contributes to the hypoxia formation in VH. The external influx of anthropogenic nutrients and organic matter through C2 further enhances the bottom water hypoxia in VH by stimulating phytoplankton bloom and microbial consumption of oxygen in water columns and sediments. Although the horizontal oxygen influx to VH is weak, the comparatively strong vertical mixing in C3 facilitates the replenishment of bottom water in the VH, mitigating bottom hypoxia. Locally in the VH, sediment oxygen demand is the dominant biogeochemical contributor (~93%) to hypoxia formation, while the contribution of water column remineralization is relatively minor (~6-7%). In general, vertical diffusion serves as the largest source (~57%) of DO in the VH because of the strong vertical DO gradient, whereas vertical motion ranks the second largest source of DO (~24%) and serves as a critical physical factor regulating the oxygen budget of the entire VH. In the spatial constriction area where the vertical DO gradient is weak, the magnitude of vertical motion exceeds vertical diffusion to become the largest source of DO (~48%).